Factors Associated with the Abandonment of Exclusive Breastfeeding before Three Months - Esmeralda Santacruz-Salas; Antonio Segura-Fragoso; Ana Isabel Cobo-Cuenca; Juan Manuel Carmona-Torres; Diana P. Pozuelo-Carrascosa; José Alberto Laredo-Aguilera (MDPI AG, 2020)
The commencement and maintenance of exclusive breastfeeding (EB) are dependent on several mother-infant factors. To analyse the prevalence of EB during four different periods and to analyse the factors that can affect its maintenance, we performed a prospective, observational, longitudinal study of 236 mothers and their child between 37 and 42 weeks of gestation and weighing more than 2.5 kg. Four interviews were conducted (T1: on discharge, T2: at 15 days, T3: at one month, T4: at three months). The results showed that EB decreased considerably at three months (69.5% vs. 47.46%). The factors that reduced the risk of abandonment were as following: having decided before giving birth that one wants to offer breastfeeding (T2: odds ratio (OR): 0.02, p = 0.001), T3 (OR: 0.04, p = 0.001) and T4 (OR: 0.07, p = 0.01)) and having previous experience with EB (T2 (OR: 0.36, p = 0.01), T3 (OR: 0.42 p = 0.02) and T4 (OR: 0.51, p = 0.03)). The factors that increased the risk of EB abandonment were offering feeding bottles in the hospital (T2 (OR: 11. 06, p = 0.001); T3 (OR: 5.51, p = 0.001) and T4 (OR: 4.43, p = 0.001)) and thinking that the infant is not satisfied (T2 (OR: 2.39, p = 0.01) and T3 (OR: 2.34, p = 0.01)). In conclusion, the abandonment of EB in the first three months is associated with sociodemographic and clinical variables and psychological factors such as insecurity and doubts of the mother during the process and the absence of a favourable close environment.